Evaluation of a Real‐Time Knowledge Exchange Network Supporting Syphilis Rapid Testing and Immediate Treatment in Seven Public Health Units in Ontario, Canada - Megan Ann Carter; Sara Tryon; Mary Southall; Kandace Belanger; Mary France Caron‐Bruneau; Anne Charron; Sandra Dereski; Michael Evans; Natasha Larkin; Kassandra Plante; Melanie St. John; Nicole Szumlanski; et al. (Learning Health Systems, 2026)
ABSTRACT Introduction The Syphilis Point of care Rapid testing and Immediate Treatment Evaluation (SPRITE) is a collaborative, community‐based initiative that strengthens syphilis prevention and control in Ontario, Canada through flexible outreach nursing and point‐of‐care testing (POCT) and immediate treatment. Seven public health units (PHUs) partnered with 86 community‐based organizations (CBOs) to deliver syphilis/HIV POCTs in underserved settings. This study evaluated a real‐time knowledge exchange network that supported syphilis POCT implementation and capacity‐building across PHUs and CBOs in Ontario. Methods The evaluation was a mixed‐methods case study using surveys and interviews focusing on the community of practice (CoP), community engagement, and knowledge mobilization. It considers SPRITE CoP activities from beginning of implementation (mid 2023) to the Fall of 2025. Results The CoP, consisting of public health nurses, researchers, and knowledge specialists, supported engagement, co‐development, and peer learning. Members shared lessons learned, built partnerships, and supported each other in navigating challenges. Flexibility in funding allowed innovation by CoP members in their CBO engagement efforts but also created some uncertainty and possible confusion. CoP members were overall satisfied with CoP functioning, and CBOs surveyed appeared knowledgeable and engaged in SPRITE. Discussion The CoP model, while distinct from traditional public health CoPs, proved effective in fostering engagement, resource development, and knowledge mobilization. Lessons learned and tools developed provide guidance for future POCT efforts. Improvements should include clearer goals, stronger facilitation, and structured engagement strategies. Addressing funding stability, particularly for POCT services and CoP management roles, is essential. Strengthening CBO partnerships through incentives and bi‐directional information sharing will further enhance POCT and syphilis prevention. This evaluation underscores the importance of flexible yet accountable approaches to knowledge mobilization and POCT implementation in diverse public health contexts. Continued investment in collaborative networks like SPRITE remains critical to advancing syphilis elimination efforts across Ontario.